Comparison of femoral neck system to multiple cancellous screws and dynamic hip screws in the treatment of femoral neck fractures. (April 2023) - Xu, Xiangyu; Fan, Jixing; Zhou, Fang; Lv, Yang; Tian, Yun; Ji, Hongquan; Zhang, Zhishan; Guo, Yan; Yang, Zhongwei; Hou, Guojin
Highlights: Femoral neck system, multiple cancellous screws, and dynamic hip screws are effective for femoral neck fractures. Femoral neck system is a simpler operation, with earlier weight-bearing time, than multiple cancellous screws. The main advantage of femoral neck system over dynamic hip screws is a minimally invasive operation. Abstract: Objective: To compare the short-term outcomes of the femoral neck system (FNS) with multiple cancellous screws (MCS) and dynamic hip screws (DHS) in the treatment of femoral neck fractures. Methods: A retrospective analysis was performed on 157 patients with fresh femoral neck fractures treated with FNS (from September 2019 to October 2020), MCS, and DHS (from January 2018 to October 2020). According to internal fixation methods, all patients were divided into the FNS group (54 cases), MCS group (51 cases), and DHS group (52 cases). Demographic data were also collected, recorded, and compared, including the follow-up time, days of hospitalization, operation time, blood loss, intraoperative fluoroscopy times (IFT), weight-bearing time (WBT), length of femoral neck shortening (LFNS), Harris hip score, and complications (such as internal fixation failure, bone nonunion, and avascular necrosis of the femoral head) between the three groups. Results: Overall, 157 patients with a mean age of 61.8 (range, 18–89) years were analyzed. In the FNS group, IFT (median 10.5) was significantly lower than that in the MCS group (median 21) and DHS group (median 20.5) ( P <0.05), and WBT was significantly earlier than that of the MCS group ( P <0.05). In the FNS group, the median hospitalization time, operation time, and blood loss were 2 (2, 4) days, 45 (40–59) min, and 30 (20, 50) ml, respectively. They were all significantly less than 3.5 (3, 6) days, 72 (55–88.75) min, and 50 (30, 50) ml in the DHS group, respectively ( P < 0.05). There was no statistical difference in LFNS, quality of reduction, internal fixation failure rate, and Harris hip score at the latest follow-up ( P >0.05). No surgical complications such as incision infection, deep infection, pulmonary embolism, or femoral head necrosis were found in any of the three groups. Conclusion: FNS, MCS, and DHS are all effective for femoral neck fractures. However, a lower IFT of FNS shortens the operation time. Compared to MCS, FNS has the advantages of being a simple operation, with early WBT; compared to DHS, a minimally invasive operation is the main advantage of FNS.